Formation of the Institution of the Commissioner for Human Rights (Ombudsman) in the Republic of Abkhazia and in the Russian Federation - A. V. Loginov (Московский журнал международного права, 2018)
Introduction. The main value of legal democratic states is the protection of human and civil rights and freedoms. For this purpose, the state forms specialized bodies – courts, as well as a specialized body – the Human Rights Ombudsman (ombudsman). In this article, the theory of the institution of the Ombudsman for Human Rights is being considered. The study of the emergence of the institution of the human rights ombudsman in the territories of the Republic of Abkhazia and the Russian Federation is primarily due to the proximity of the legal systems of both states and the vast amount of Abkhazia's imposition as provisions of Russian regulatory legal acts, experience in their enforcement, as well as experience in building democratic state authorities. To consider this study as authentic is possible for a number of reasons: First, a comparative plan, in the study of foreign experience of the institution of the Commissioner for Human Rights. Second, given the degree of influence of the Russian experience of building a legal democratic state on Abkhazia, this study also presents some retrospective value in studying the Russian institution of the Ombudsman for Human Rights under conditions of limited funding. Third, taking into account the fact that 90% of the inhabitants of the Republic of Abkhazia are citizens of the Russian Federation – the study of the problems of protecting their rights and freedoms is of great interest for Russian legal science.Materials and methods. The methodological basis of the research was general scientific (sociological, systemic, etc.) and special (comparative legal, formal-legal, historical-legal etc.) methods of cognition.Research results. As a result of the retrospective analysis of the establishment of the institution of the authorized person for human rights in the territory of the Russian Federation and the Republic of Abkhazia, it was revealed that the institution of the Commissioner for Human Rights on the territory of the Russian Federation is an important body called to ensure the protection of human and civil rights and freedoms (primarily from administrative arbitrariness); that the institution of the Ombudsman for Human Rights in the territory of the Republic of Abkhazia had previously been only formally declarative, and after the reform, designed to increase the protection of human and civil rights and freedoms, was not able to function for any number of reasons: lack of material and technical support. Unfortunately, the lack of this institution, together with a number of problems of the judiciary, does not allow to fully protect the interests, rights and freedoms of citizens of the Republic of Abkhazia. At the same time, considering the dual citizenship of these citizens, a number of questions and the inactivity of the Russian authorities to protect the citizens living permanently abroad (in this territory) raise a number of questions.Discussion and conclusions. The analysis made it possible to identify a number of reasons that prevented the establishment of the Ombudsman institution in the Republic of Abkhazia, which adversely affects the human rights situation of people living n Abkhazia (including Russian citizens). A number of proposals have been put forward to ensure the level of protection of human rights in the territory of the Republic of Abkhazia.